Unravelling taxonomic uncertainties among balloon vine species within the genus Cardiospermum using a molecular approach - Gildenhuys, Enelge (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.